Effects of bovine pituitary extract on testosterone levels, androgen receptor expression, sperm quality, and testicular morpho function in male rats - JULI MELIA; TEUKU ARMANSYAH; TONGKU NIZWAN SIREGAR; CUT INTAN NOVITA; HUSNURRIZAL HUSNURRIZAL; SRI WAHYUNI; IQRANA QARANI AHMAD; ILHAM RAHMAN EFLIANDI; MIFTAHUL HADDIAH; ZAININA NADHILAH MARYAM (Smujo International, 2026)
Testosterone plays a central role in spermatogenesis and male reproductive function, primarily through its interaction with androgen receptors (AR) in testicular cells. Optimizing AR expression is therefore essential for maintaining normal testicular activity and ensuring high sperm quality. Bovine pituitary extract (BPE), which contains key reproductive hormones such as follicle-stimulating hormone (FSH) and luteinizing hormone (LH), has the potential to modulate endocrine function and enhance spermatogenesis. This study aimed to evaluate the effects of BPE administration on plasma testosterone levels, AR expression, sperm quality, and testicular morpho function in male Wistar rats. Animals were divided into a control group and treatment groups receiving intraperitoneal BPE injections over 1–6 weeks. The findings revealed that BPE did not significantly affect circulating testosterone levels. However, AR expression in Leydig cells increased significantly after two weeks of treatment. Improvements were also observed in sperm quality, including higher concentration and motility, along with reduced abnormalities. Additionally, testicular structure showed enhancement, reflected by increased seminiferous tubule diameter and germinal epithelial thickness. Overall, BPE administration improves male reproductive performance by enhancing AR expression, spermatogenesis, and testicular structure without altering systemic testosterone levels.